2017
DOI: 10.1021/acsnano.7b04734
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Lipids in RNA Interference Therapeutics

Abstract: RNA is emerging as a potential therapeutic modality for the treatment of incurable diseases. Despite intense research, the advent to clinical utility remains compromised by numerous biological barriers, hence, there is a need for sophisticated delivery vehicles. In this aspect, lipid nanoparticles (LNPs) are the most advanced platform among nonviral vectors for gene delivery. In this review, we critically review the literature and the reasons for ineffective delivery beyond the liver. We discuss the toxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
140
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 109 publications
4
140
0
Order By: Relevance
“…These results demonstrated that ethanolamine and hydroxylamine linkers are more efficient dominators compared to hydrazine linkers in gene silencing. These results are supported by previous work demonstrating that LNPs showing surface p K a value of 5.5 to 7.0 exhibiting efficient in vivo gene silencing . We measured the p K a values of lipid‐2, lipid‐6, lipid‐8, and lipid‐10 LNPs (Figure S8, Supporting Information).…”
supporting
confidence: 86%
See 3 more Smart Citations
“…These results demonstrated that ethanolamine and hydroxylamine linkers are more efficient dominators compared to hydrazine linkers in gene silencing. These results are supported by previous work demonstrating that LNPs showing surface p K a value of 5.5 to 7.0 exhibiting efficient in vivo gene silencing . We measured the p K a values of lipid‐2, lipid‐6, lipid‐8, and lipid‐10 LNPs (Figure S8, Supporting Information).…”
supporting
confidence: 86%
“…However, siRNAs are unable to cross the cell membrane due to their polyanionic nature, therefore suitable delivery strategies are required to access the target cell cytoplasm . Nonviral gene therapy is the most promising strategy to deliver nucleic acids with less or no immunogenic responses compared to viral gene delivery . Lipid nanoparticles (LNPs) containing ionizable amino lipids are the most advanced nonviral delivery platforms for negatively charged nucleic acids .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Formed by assembly of lipids in aqueous solution, [11] liposomes have long been a scientific curiosity not only as model systems for understanding the cell membrane systems, [12] but also due to their capability to encapsulate hydrophobic or hydrophilic active molecules as microcarriers in drug delivery, gene therapy, and sensing. [13][14][15][16] Vesicle polymer gel forms by mixing vesicles solution with water-soluble polymer bearing hydrophobic motifs, with the vesicles serving as multivalent crosslinkers to bridge the adjacent polymer chains. [17,18] The hydrophobic effect is the main driven force in the solution-to-gel process, and the dynamic crosslinking may facilitate the formation of injectable hydrogels which are highly important in many biomedical applications.…”
Section: Doi: 101002/smll201704039mentioning
confidence: 99%